Pengaruh Lingkungan Kerja, Disiplin Kerja Dan Komunikasi Terhadap Kinerja Pegawai Kantor Kelurahan Jatimulya - Ajijah Jumani; Ni Nyoman Sawitri; Adi Wibowo Noor Fikri; Dewi Puspaningtyas Faeni; Indah Rizki Maulia (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The research method used is quantitative research, this research is used to test populations and samples with the aim of testing predetermined hypotheses. Data analysis using Smart PLS 3.0 software. The results of the path coefficient hypothesis test have a P value of > 0.000 or > 0.05 and the t statistical value of the work environment has a value of 5.192 or > 1.96 so that it is stated that there is a significant influence between work environment variables on employee performance. Based on the results of the path coefficient hypothesis test, there is a P-value of 0.002 or <0.05 and the work discipline t-statistic value has a value of 3.095 or >1.96, so it is stated that there is a significant influence between the work discipline variable on employee performance. Based on the results of the path coefficient hypothesis test, there is a P-value of 0.000 or <0.05 and the communication t-statistic value has a value of 3.630 or >1.96, so it is stated that there is a significant influence between work discipline. variables on employee performance. Based on the results, the coefficient of determination (R Square) in the first substructure is 0.993, which means that simultaneously the total influence of the work environment, work discipline and communication on employee performance is 99.3%.